Applying the Visual teaching method to the teaching of the electrical engineering with students belong non- electrical engineerings. - Bui , Văn Hồng; Dang , Văn Thành (Journal of Technical Education Science, 2008)
The visual teaching is an active teaching and learning, it is suitable to transfer the concrete and abstract knowledge, such as the electrical engineering subject. With a lot of lively pictures, student’ll get the knowledge more easily, so it’ll get the higher effect in teaching and studying